Political partisanship, trait empathy, and social justice concerns in a representative sample of Californians - Andres G. Martinez (Discover Psychology)
Abstract The current study provides an analysis of a representative sample of Californians (N = 875) to obtain insight into the nature of emotional empathy across the political divide. Although Democrats, Republicans, and Independents differed in average trait emotional empathy levels, the magnitudes of these differences were not large. Analysis showed that although all political categories showed some degree of empathy, the target of this empathy varied by political party. Specifically, Democrats’ and Independents’ empathic tendencies were linked to social justice concerns. In contrast, Republicans’ empathic tendencies were disconnected from this domain. These findings provide evidence that—in California and perhaps beyond—political affiliation predicts who is seen as worthy of empathy. Discussion explores the implications of these findings for political polarization and cooperation across partisan categories.